12th European Conference on Antennas and Propagation (EuCAP 2018) 2018
DOI: 10.1049/cp.2018.0446
|View full text |Cite
|
Sign up to set email alerts
|

Simplified Molecular Absorption Loss Model for 275-400 Gigahertz Frequency Band

Abstract: This paper focuses on giving a simplified molecular absorption loss model for a 275-400 GHz frequency band, which has significant potential for variety of future short and medium range communications. The band offers large theoretical data rates with reasonable path loss to theoretically allow even up to kilometer long link distances when sufficiently high gain antennas are used. The molecular absorption loss in the band requires a large number of parameters from spectroscopic databases, and, thus, the exact m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
88
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(91 citation statements)
references
References 10 publications
0
88
0
Order By: Relevance
“…h f respectively model the deterministic path gain, the misalignment fading and the stochastic path gain. The deterministic path gain coefficient can be expressed as h l = h f l h al , where h f l models the propagation gain according to the Friis equation, while h al stands for the molecular absorption gain and can be evaluated as in [5]. For the pointing errors, the probability density function (PDF) of the channel coefficient, h p , can be obtained as in [2].…”
Section: Introductionmentioning
confidence: 99%
“…h f respectively model the deterministic path gain, the misalignment fading and the stochastic path gain. The deterministic path gain coefficient can be expressed as h l = h f l h al , where h f l models the propagation gain according to the Friis equation, while h al stands for the molecular absorption gain and can be evaluated as in [5]. For the pointing errors, the probability density function (PDF) of the channel coefficient, h p , can be obtained as in [2].…”
Section: Introductionmentioning
confidence: 99%
“…Next, by substituting (14) into (10), the ergodic capacity can be expressed as (15) or, by using [28, eq. (15.1.1)], as…”
Section: Performance Analysismentioning
confidence: 99%
“…In more detail, in [14], the authors presented a novel propagation model for THz nano-scale communications. Additionally, in [15], a simplified path-loss model for the 275 − 400 GHz band was introduced. Furthermore, in [16], a multi-ray THz propagation model was presented, while, in [17], a propagation model for intrabody nano-scale communications was provided.…”
Section: Introductionmentioning
confidence: 99%
“…Scanning the technical literature, a great amount of research effort has been put on modeling and evaluating the performance of both THz [4]- [11] and RF wireless systems (see e.g., [12] and references therein). In particular, in [4], the authors reported a novel THz-band propagation model, whereas, in [5], a simplified molecular absorption loss model was delivered. The latter model was used in [6] for the quantification of the THz link capacity.…”
Section: Introductionmentioning
confidence: 99%